2015
DOI: 10.1007/s11145-015-9549-0
|View full text |Cite|
|
Sign up to set email alerts
|

Writing quality predicts Chinese learning

Abstract: To examine the importance of manual character writing to reading in a new writing system, 48 adult Chinese-as-a-foreign-language students were taught characters in either a character writing-to-read or an alphabet typing-to-read condition, and engaged in corresponding handwriting or typing training for five consecutive days. Prior knowledge of orthography and phonology was assessed before training. At the end of each training day, improved orthographic quality was assessed via increased skill in producing Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…Because low-level visual and motor processes were well controlled, the results of this study could be the specific brain substrates for Mandarin Chinese writing. In addition, previous behavioral studies have demonstrated that copying characters or symbols is uniquely essential for Chinese reading skill (Tan et al, 2005b ; Guan et al, 2015 ; Kalindi et al, 2015 ); thus, our findings offer valuable information for understanding the relationship between copying skill and reading in Chinese.…”
Section: Discussionsupporting
confidence: 53%
“…Because low-level visual and motor processes were well controlled, the results of this study could be the specific brain substrates for Mandarin Chinese writing. In addition, previous behavioral studies have demonstrated that copying characters or symbols is uniquely essential for Chinese reading skill (Tan et al, 2005b ; Guan et al, 2015 ; Kalindi et al, 2015 ); thus, our findings offer valuable information for understanding the relationship between copying skill and reading in Chinese.…”
Section: Discussionsupporting
confidence: 53%
“…Languages with alphabetic orthographies (e.g., English and Korean) have a systematic correspondence between graphemes and phonemes, whereas languages with nonalphabetic orthographies (e.g., Chinese) do not have the same reliable sublexical structure. In the case of Chinese, directing attention toward phonology has been shown to benefit the learning of phonological form, but not the learning of orthographic form (e.g., Cao et al, 2017;Guan, Liu, Chan, Ye, & Perfetti, 2011;Guan, Perfetti, & Meng, 2015;Lagarrigue et al, 2017). For example, Lagarrigue and colleagues recently reported a study in which native French speakers who were enrolled in a basic Chinese university course learned a small set of Chinese characters in the laboratory.…”
Section: Directing Attention Toward Phonology Improves Learningmentioning
confidence: 99%
“…Previous studies on Chinese (Tan et al, 2005;Xu, Chang, Zhang, & Perfetti, 2013) have also suggested that reading could depend on writing in lower elementary students. An experimental study on Chinese writing practice (Guan, Perfetti, & Meng, 2015) showed that handwriting improvement predicted reading improvement. Some of these studies revealed that high quality representation of words in spelling positively affected reading (Perfetti, 2007).…”
Section: Characteristics and Studies Of Chinesementioning
confidence: 99%